Implementasi Pembelajaran Berbasis HOTS (Higher Order Thinking Skills) pada Pembelajaran Tematik - Wahyuningsih, Agustina; Sumardjoko, Bambang; Dessty, Anatry (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this study was to explore the HOTS-based learning planning process in thematic learning. Exploring the process of implementing HOTS-based learning in thematic learning. Exploring the HOTS-based learning evaluation process in thematic learning at Bakalan Nguntoronadi Elementary School, Wonogiri Regency. The research was conducted at Bakalan Nguntoronadi Public Elementary School, Wonogiri Regency in the Odd Semester of the 2022-2023 academic year. The research subjects were people who were involved in implementing HOTS-based learning in thematic learning. Data collection techniques with interviews and documentation. Data analysis using descriptive analysis. The results showed that planning learning methods by considering suitability with learning objectives, suitability with learning materials, suitability with the media, tools, materials, and learning resources used, students' abilities, students' learning styles, duration of time available, and the possibility of freedom teacher in varying the methods that will be used by the teacher, and the interaction of teachers with students, students with teachers, and students with students. The implementation of HOTS-based thematic learning is carried out through the application of learning models based on student activity including the discovery/inquiry learning model, the Problem-based Learning (PBL) model, and the Project-based Learning model. The implementation of HOTS-based thematic learning is constrained by the teacher's lack of understanding of the HOTS concept, so that learning carried out using inquiry, PBL, and project based learning models has not been able to improve higher-order thinking skills. HOTS-based learning evaluations are: (1) Measuring higher-order thinking skills, (2) based on Contextual Problems, (3) aspects of assessment in the form of attitude assessment, (4) are divergent, and (5) use multiple representations.